2003
DOI: 10.1074/jbc.m210783200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Murine Tumor Necrosis Factor Receptor Locus That Contains Two Novel Murine Receptors for Tumor Necrosis Factor-related Apoptosis-inducing Ligand (TRAIL)

Abstract: Tumor necrosis factor (TNF) ligand and receptor superfamily members play critical roles in diverse developmental and pathological settings. In search for novel TNF superfamily members, we identified a murine chromosomal locus that contains three new TNF receptorrelated genes. Sequence alignments suggest that the ligand binding regions of these murine TNF receptor homologues, mTNFRH1, -2 and -3, are most homologous to those of the tumor necrosis factor-related apoptosisinducing ligand (TRAIL) receptors. By usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 40 publications
2
96
0
1
Order By: Relevance
“…5,13,14 Thus, in KB cells that express TRAILR1 and TRAILR2, non-crosslinked TRAIL trimers already significantly induce cell death via the TRAILR1, whereas TRAILR1-mediated cell death is not relevant in the murine L929 cell line, because in mice only a homolog of human TRAILR2 exists. 15,16 In fact, in human Jurkat cells, which express only TRAILR2, noncrosslinked Flag-hTRAIL(95-291) is also practically inactive (Figure 2c). …”
Section: Resultsmentioning
confidence: 96%
“…5,13,14 Thus, in KB cells that express TRAILR1 and TRAILR2, non-crosslinked TRAIL trimers already significantly induce cell death via the TRAILR1, whereas TRAILR1-mediated cell death is not relevant in the murine L929 cell line, because in mice only a homolog of human TRAILR2 exists. 15,16 In fact, in human Jurkat cells, which express only TRAILR2, noncrosslinked Flag-hTRAIL(95-291) is also practically inactive (Figure 2c). …”
Section: Resultsmentioning
confidence: 96%
“…Following these observations, we monitored the dynamics of murine TRAIL receptor-2 after transplantation, this being the only known murine receptor for TRAIL that corresponds to human DR5. 20,21 We found that signaling by the murine receptor is trophic in nature.…”
Section: Introductionmentioning
confidence: 93%
“…[17][18][19] Among the known five TRAIL receptors, DR4 (TRAIL-R1) and DR5 (TRAIL-R2) are associated with transduction of apoptotic signals in humans, 16 whereas mice express only TRAIL-R2. 20,21 Although mRNA encoding TRAIL receptors DR4 and DR5 is frequently detected in CD34 þ progenitors, these cells were insensitive to apoptosis 22,23 even in the presence of low doses of doxorubicin. 24 Consistently, infusion of soluble TRAIL into rodents was not associated with gross abnormalities in hematopoiesis, 25,26 and TRAIL neither induced nor impaired the clonogenic activity of human hematopoietic progenitors in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, because TRAIL kills neoplastic and normal human prostate epithelial cells (18) via activation of the apical caspases (43), we examined its role in TGFh1-mediated apoptosis. Human TRAIL can bind two death-inducing receptors, DR4 and DR5, as well as three decoy receptors and OPG (44), but the DR4 receptor does not exist in rodents (45). Fc fusions of the extracellular domains of these receptors block TRAIL-induced cell death (18).…”
Section: Death Ligand Blockers Do Not Inhibit Tgfb1-induced Apoptosismentioning
confidence: 99%